Penyuluhan Pemilahan dan Pengolahan Limbah Kain - Martinus Edy Sianto; Dian Retno S.D; Jaka Mulyana; Julius Mulyono; Irene Karijadi; Albert Gunadhi (Jurnal Ragam Pengabdian, 2025)
In the preliminary meeting with SMPK St. Agnes as a partner, it was known that the partner had implemented restrictions on the use of plastic materials, but had never received counseling material on the dangers of textile waste. This activity aims to increase awareness and knowledge of partners regarding the concept of sustainability, the hazards of fabric waste and how to sort and treat it. In this activity, various types of textile materials, their properties and how to utilize and process them after they are no longer used were explained. This activity also involved PT Panjimas as a company that processes textile waste into yarn raw materials, which was involved as one of the speakers. This activity was attended by 43 participants consisting of 20 students and 23 teachers/employees. The evaluation was carried out using a questionnaire. After the activity, the participants stated that there was an increase in awareness of the hazards of textile waste with details, 25 respondents were very aware, 16 were quite aware, and only 2 were slightly aware. No respondents felt that they had not changed. This community service activity succeeded in achieving its objectives, but improvements in methods, duration, and approaches were needed to ensure a greater and more sustainable impact in the future.